Strategi Nafkah Petani di Era Pandemi Covid-19 (Studi Kasus di Desa Wonorejo dan Desa Kragan, Kecamatan Gondangrejo, Kabupaten Karanganyar) - Alfira Rahma Nursita Haerna; Suwarto Suwarto; Widiyanto Widiyanto (Jurnal Indonesia Sosial Sains, 2022)
The Covid-19 pandemic is a challenge faced by all sectors, one of which is the agricultural sector. Gondangrejo Sub-district is one of the sub-districts in Karanganyar Regency which according to Karanganyar Health Service data in 2021 with the highest number of positive Covid-19 victims reaching 1,608 people as of September 30, 2021. The impact of the Covid-19 pandemic was felt by almost all circles, including rural communities. This condition encourages people to carry out livelihood strategies to be able to meet the needs of their families during the Covid-19 pandemic. This study aims to examine how the impact of the Covid-19 pandemic, livelihood strategies and the impact of the strategies carried out by farmers during the Covid-19 pandemic were. The research method used is qualitative with a case study approach. The research location was determined purposively in Wonorejo and Kragan Villages, Gondangrejo District, Karanganyar Regency. Determination of informants is done by purposive and snowball sampling. The validity of the data using triangulation of sources and techniques. The results showed that the Covid-19 pandemic had an impact on agricultural physical capital, financial capital, and social capital for farmers in Wonorejo and Kragan villages. The livelihood strategies carried out by farmers in Wonorejo and Kragan villages during the Covid-19 pandemic are on-farm, off-farm, and non-farm. The livelihood strategies that have been carried out by farmers are able to meet daily basic needs during the Covid-19 pandemic and are able to survive in the face of the Covid-19 pandemic.